2021
DOI: 10.1186/s12889-021-10194-0
|View full text |Cite
|
Sign up to set email alerts
|

Impact of macro-socioeconomic determinants on sustainable perinatal health care in Portugal: a qualitative study on the opinion of healthcare professionals and experts

Abstract: Background The WHO identified the importance of macro-socioeconomic determinants and political context as interlinked key factors affecting healthcare quality and health equity. As a response to the recent economic and financial crisis, Portugal approved in 2011 the Economic Adjustment Programme (EAP) to obtain financial assistance from the Troika in order to reduce public debt. This study aims to analyse the impact of the economic crisis and the EAP on perinatal healthcare quality for very pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Those factors have been associated with consequential risks posed to health, especially to child health,4 59 60 mental health61–63 and chronic illnesses,64 differing across socioeconomic groups,12 regions57 and time frames 4 10. The multifactorial impact of the Great Recession61 on maternal and perinatal health and mortality rates was observed in adverse socioeconomic consequences,11 61 65 altered motherhood,66 declining fertility and self-rated health,67 deteriorated mental health, especially for low-income groups,12 and lowered perceived social support during pregnancy 33…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Those factors have been associated with consequential risks posed to health, especially to child health,4 59 60 mental health61–63 and chronic illnesses,64 differing across socioeconomic groups,12 regions57 and time frames 4 10. The multifactorial impact of the Great Recession61 on maternal and perinatal health and mortality rates was observed in adverse socioeconomic consequences,11 61 65 altered motherhood,66 declining fertility and self-rated health,67 deteriorated mental health, especially for low-income groups,12 and lowered perceived social support during pregnancy 33…”
Section: Discussionmentioning
confidence: 99%
“…As described above, the diverse magnitude and duration of the socioeconomic effects of the recession and governmental response across European member states affected perinatal outcomes across the selected countries to a different extent 11. Austerity measures have been discussed to have harmed maternal and child health,33 93 perinatal healthcare quality,33 93 intensified health inequalities94 and increased material deprivation across Europe 59. However, other major contemporary events (eg, increased influenza and the 2015 heatwave in Spain) during the post-austerity period may have prevented identifying a possible delayed effect of austerity policies in slowing mortality decline 95.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The demand and pressure of human resources is related to an aging workforce and the overall shortage of human resources, which remains a major obstacle to the optimal functioning of the NHS [29,31]. A recent study revealed that the 2008 economic crisis and austerity measures were perceived to have aggravated the deficiency in human resources in Portugal [32,33]. Confirming this, a study in 2016 reported that many medical doctors declared that they would opt to migrate due to a changed working environment induced by the crisis and austerity measures [34].…”
Section: Discussionmentioning
confidence: 99%